Tellimya tehuelcha, new species: First record of tellimya brown, 1827, in South America (Bivalvia: Lasaeidae), with notes on life history and reproduction - Zelaya, Diego Gabriel (2012)
Fil: Zelaya, Diego Gabriel. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Biodiversidad y Biología Experimental; Argentina